On the use of the type I Gumbel distribution to assess risks given floods - Stefanyshyn, D.V. (Математичне моделювання в економіці, 2018)
In this article, there is considered the possibility of using the type I Gumbel distribution as one among alternative forecasting models in assessing flood risks at rivers, which is carried out based on forecasting of maximum hydrological characteristics according to hydrological observations. Examples are given and analyzed are the results of forecasting of the maximum water discharges of low exceedance probabilities, which were obtained with the use of the type I Gumbel distribution and other probability distributions for the Dnieper (the Vyshgorod water level gauge) and the Stryi River (the Verkhnye Syn’ovydne water level gauge). In addition to the analytical distributions for the Dnieper River, a generalized probability distribution function obtained by modeling within the fuzzy set theory was also used in the comparative analysis. The possibility of extending the scope of the practical application of the type I Gumbel distribution in forecasting hydrological maxima by logarithmic transformation is shown